2003
DOI: 10.1083/jcb.200306020
|View full text |Cite
|
Sign up to set email alerts
|

Formation of stacked ER cisternae by low affinity protein interactions

Abstract: The endoplasmic reticulum (ER) can transform from a network of branching tubules into stacked membrane arrays (termed organized smooth ER [OSER]) in response to elevated levels of specific resident proteins, such as cytochrome b(5). Here, we have tagged OSER-inducing proteins with green fluorescent protein (GFP) to study OSER biogenesis and dynamics in living cells. Overexpression of these proteins induced formation of karmellae, whorls, and crystalloid OSER structures. Photobleaching experiments revealed that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

29
533
4
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 427 publications
(568 citation statements)
references
References 49 publications
29
533
4
2
Order By: Relevance
“…Latrunculin B did induce dissociation of the OCs and their transformation into tubular membranes (Figure 2d; also see Supplemental Movie 3). These data support the premise that the DiHcRED-MAL OCs are formed by cross-linking of the upper and lower surface membranes by the tandem HcRED dimers, as reported for the interaction of ER-retained anti-parallel GFP-tagged proteins (Snapp et al, 2003). Cross-linking of the upper and lower surface membranes may potentially be initiated by the formation of intermolecular dimers made up of two closed or open conformation tandem dimers from opposing surface membranes, as demonstrated in the scheme in Figure 2e.…”
Section: Characterization Of Dihcred-mal Clusterssupporting
confidence: 89%
See 1 more Smart Citation
“…Latrunculin B did induce dissociation of the OCs and their transformation into tubular membranes (Figure 2d; also see Supplemental Movie 3). These data support the premise that the DiHcRED-MAL OCs are formed by cross-linking of the upper and lower surface membranes by the tandem HcRED dimers, as reported for the interaction of ER-retained anti-parallel GFP-tagged proteins (Snapp et al, 2003). Cross-linking of the upper and lower surface membranes may potentially be initiated by the formation of intermolecular dimers made up of two closed or open conformation tandem dimers from opposing surface membranes, as demonstrated in the scheme in Figure 2e.…”
Section: Characterization Of Dihcred-mal Clusterssupporting
confidence: 89%
“…The details of DiHcRED-MAL OC formation are not completely understood. However, it is reminiscent of the previously reported organized smooth ER, known to consist of cubic-phase membranes generated by weakly dimerizing antiparallel FP-tagged ER proteins (Snapp et al, 2003;Almsherqi et al, 2006). The MAL tetra-spanning moiety is important in OC formation.…”
Section: Discussionmentioning
confidence: 85%
“…Green fluorescent protein (GFP) in previously described TorA-GFP plasmids (Naismith et al, 2004) was changed to monomeric GFP (mGFP) by sitedirected mutagenesis of L221K in GFP (Snapp et al, 2003b). TorA-TagRFP was made by transferring TorA mutants excised with XhoI and EcoRI from EGFP-N1 into a RFP-N1 vector containing TagRFP (Merzlyak et al, 2007).…”
Section: Plasmidsmentioning
confidence: 99%
“…To assess the specificity of this phenomenon, we asked whether overexpressing LULL1 would cause another ER protein to redistribute, and conversely, whether introducing another ER protein would change the localization of TorA. For this analysis, we used Sec61␥ tagged with GFP, which, similarly to LULL1, is a mobile single-pass transmembrane protein of the ER (Snapp et al, 2003b). We found that expressing LULL1-myc did not change the distribution of mGFP-Sec61␥ between bulk ER and NE ( Figure 1D) and that introducing mGFP-Sec61␥ did not cause TorA to redistribute to the NE ( Figure 1E).…”
Section: Dynamic Regulation Of Tora Distribution By Lull1mentioning
confidence: 99%
“…These globular structures were presumed to be karmalle, which are stacks of ER cisternae and are often induced by Cb 5 when overexpressed in eukaryotic cells. 7,12,13 While karmalle do not induce the unfolded protein response, 13 any BY-2 cells exhibiting these types of structures were discarded from our analysis of Fad3-GFP-Cb5 protein half-life. Investigation of protein degradation rates for the various fusion constructs revealed that GFP-Cb5 was moderately stable in plant cells, and notably, the degradation rate was not appreciably affected by inclusion of the proteasomal inhibitor MG132 (Fig.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%